(untitled) (Italian Journal of Public Health, 2009)
Background: The predicted ageing rate of the Italian population is one of the highest worldwide and this condition is expected to produce a growing increase in pharmaceutical expenditure. The objective of this study was to assess whether or not off-patent drugs could counterbalance the economic effects generated by the aging of the Italian population in the next ten years. Methods: On the basis of the predicted ageing rate of the Italian population for the period 2008-2018, the average annual cumulative increase of pharmaceutical expenditure and potential savings generated by the future loss of patent coverage have been considered in order to identify the year of the Breakeven Point. Results: The economic effect induced by the progressive ageing of population produces an average of 0.94% cumulative increase in local pharmaceutical expenditure per year, corresponding to an incremental pharmaceutical expenditure of about € 116 millions per year. A number of 509 brands (103 active substances) will lose their patent coverage in the next 10 years. Considering both the present legislation and a level of price reduction, after patent expiration, corresponding to 40%, it is predicted that the Breakeven Point will be achieved at the end of 2011. Conclusions: In this study, a long term balance between the predictable increase of pharmaceutical expenditure induced by the ageing of Italian population and savings produced by future off-patent drugs was not established. In order to assure the future sustainability of pharmaceutical expenditure, this study supports the need for the development of new health policy strategies.